2022
DOI: 10.2196/35774
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Use in Pediatric Oncology and Hematology: Protocol for a Multicenter Point-Prevalence Study With Qualitative Expert Panel Assessment

Abstract: Background Because infections are a major driver of morbidity and mortality in children with hematologic or oncologic diseases, antimicrobials are frequently prescribed in pediatric oncology practice. However, excess or inappropriate use of antimicrobials is directly linked to the emergence of antimicrobial resistance. Although point-prevalence studies have examined the extent of antimicrobial use, a comprehensive qualitative evaluation of individual antimicrobial prescriptions remains lacking. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…10,11,26,27 Preterm infants have functionally less mature innate and adaptive immune systems than older children 28 predisposing these infants to infections. 7,27 Similarly, children with oncologic or hematologic diseases are predisposed to severe bacterial and antifungal diseases, 29 and antimicrobials prescribed for these patients in our study may have been to treat confirmed or suspected infections, or for medical prophylaxis. While critical risk factors of HAI in neonates, gestational age and birth weight, cannot be modified, stringent IPC measures and antimicrobial policies in vulnerable children are warranted.…”
Section: Discussionmentioning
confidence: 82%
“…10,11,26,27 Preterm infants have functionally less mature innate and adaptive immune systems than older children 28 predisposing these infants to infections. 7,27 Similarly, children with oncologic or hematologic diseases are predisposed to severe bacterial and antifungal diseases, 29 and antimicrobials prescribed for these patients in our study may have been to treat confirmed or suspected infections, or for medical prophylaxis. While critical risk factors of HAI in neonates, gestational age and birth weight, cannot be modified, stringent IPC measures and antimicrobial policies in vulnerable children are warranted.…”
Section: Discussionmentioning
confidence: 82%
“…Our study protocol recently has been published. 10 The study is reported in adherence with the STROBE statement ( Table S1 , Appendix p. 12–13 ).…”
Section: Methodsmentioning
confidence: 99%